(untitled) (Global Journal of Human-Social Science, 2017)
The Tiv are traditionally farmers by occupation. This implies that they till the soil and keep animals. These provide them with food, meat and a source of income. As agriculturalists, the roles of the or u varen iwa (black smith) and the or u gban agbe (hoe handle maker) is indispensable in the process of food production. This has to do with the fact that they produce the equipments needed for farming such as hoes, sickles, machetes, axes, knives, and hoe handles to which hoe blades are fixed for the making of heaps/mounds and lines for planting various crops. This makes these craftsmen agricultural technologists. The research adopts both the primary and secondary sources of data. This involves oral interview with blacksmiths and hoe handle makers for the primary source. For documented source the paper makes use of books, journals, newspapers and magazines.